Is routine ECC necessary in patients with HPV16 and normal cytology?. Issue 12 (24th October 2018) - Ureyen, Isin; Toptas, Tayfun; Uysal, Aysel
Abstract : Background: In the present study, we primarily aimed to correlate the colposcopy results of patients with human papillomavirus (HPV) positivity and abnormal cervical screening results. Secondarily, we attempted to define the role of endocervical curettage (ECC) in the colposcopic evaluation of patients who had normal cytology and HPV16, which is the most carcinogenic HPV type. Methods: This was a retrospective study analyzing the data of patients who had colposcopies between January 2015 and May 2016 in the Gynecological Oncology clinic of a single tertiary center. The data were evaluated to identify the pathologies in patients with HPV positivity and abnormal cervical screening results. A Colposcopic examination database was evaluated to obtain information regarding the cervical transformation zone (TZ), which was divided into three types by the International Federation for Cervical Pathology and Colposcopy. The binary variables were reported as counts and percentages. Results: A total of 1049 patients were included in the analysis. The median age of the patients was 43 (range: 21‐79). Cervical biopsies, ECC results, or both revealed cervical intraepithelial neoplasia 2+ (CIN2+: CIN2, CIN3, and invasive cancer) lesions in 22% (70/322) of the patients with HPV16 positivity, while this ratio was 8% (6/78) for patients with HPV18. CIN2+ lesions were detected in the 2.5% of patients with HPV positivity for types other than 16 and 18, as well as normal cytology. In the group of patients with HPV 16 and normal cytology, CIN2+ results were observed in the ECC of 11% of the patients whose colposcopy was normal regardless of the TZ type. Ten of the patients had invasive cancer. Conclusion: The current study provides evidence for the possible role of routine ECC in patients with HPV16, normal cytology, and a normal colposcopy.